2017
DOI: 10.2174/1381612822666160927113748
|View full text |Cite
|
Sign up to set email alerts
|

Adduct Formation and Context Factors in Drug Hypersensitivity: Insight from Proteomic Studies

Abstract: Drug hypersensitivity reactions result from the activation of the immune system by drugs or their metabolites. The clinical presentations of drug hypersensitivity can range from relatively mild local manifestations to severe systemic syndromes that can be life-threatening. As in other allergic reactions, the causes are multifactorial as genetic, metabolic and concomitant factors may influence the occurrence of drug hypersensitivity. Formation of drug protein adducts is considered a key step in drug adverse rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…Therefore, oxidative stress is a concomitant factor in numerous pathological situations requiring antibiotic administration. Oxidative stress can influence drug protein-adduct formation by multiple mechanisms, including induction of conformational alterations or oxidative modifications that can either increase or blunt the reactivity of the modified residues towards the drug, as we have recently reviewed (González-Morena et al, 2016). While exploring the impact of oxidants or reducing agents on protein modification by AX, we observed that the presence of exogenous thiol-containing molecules influenced the extent of AX-protein adduct formation.…”
Section: Introductionmentioning
confidence: 86%
“…Therefore, oxidative stress is a concomitant factor in numerous pathological situations requiring antibiotic administration. Oxidative stress can influence drug protein-adduct formation by multiple mechanisms, including induction of conformational alterations or oxidative modifications that can either increase or blunt the reactivity of the modified residues towards the drug, as we have recently reviewed (González-Morena et al, 2016). While exploring the impact of oxidants or reducing agents on protein modification by AX, we observed that the presence of exogenous thiol-containing molecules influenced the extent of AX-protein adduct formation.…”
Section: Introductionmentioning
confidence: 86%
“…Human serum albumin (HSA) can be considered the main protein target for haptenation by β‐lactams, since it is the most abundant protein in plasma, has multiple binding sites, and acts as a carrier for endogenous and exogenous compounds . To gain insight into the haptenation process, proteomic studies with HSA have been performed with different β‐lactams . Conjugation of these antibiotics is mainly driven by the nucleophilic attack of lysine amino groups from the protein to the electrophilic carbonyl group of the β‐lactam ring .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, AX reactivity and conjugation to carrier molecules have been the subject of thorough investigation [15,25]. The redox status is a major determinant of drug action and oxidative stress is a well-recognized coadjuvant factor in drug adverse reactions [14]. Moreover, the redox status and oxidative modifications can influence drug binding to carrier proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, oxidative stress is a concomitant factor in numerous pathological situations requiring antibiotic administration. Oxidative stress can influence drug protein-adduct formation by multiple mechanisms, including induction of conformational alterations or oxidative modifications that can either increase or blunt the reactivity of the modified residues towards the drug, as we have recently reviewed [14]. While exploring the impact of oxidative or reducing agents on protein modification by AX, we observed that the presence of exogenous thiol-containing molecules influenced the extent of AX-protein adduct formation.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation